HGF Mediates Clinical‐Grade Human Umbilical Cord‐Derived Mesenchymal Stem Cells Improved Functional Recovery in a Senescence‐Accelerated Mouse Model of Alzheimer's Disease. Issue 17 (6th July 2020) - Jia, Yali; Cao, Ning; Zhai, Jinglei; Zeng, Quan; Zheng, Pei; Su, Ruyu; Liao, Tuling; Liu, Jiajing; Pei, Haiyun; Fan, Zeng; Zhou, Junnian; Xi, Jiafei; et al.
Abstract: Stem cells have emerged as a potential therapy for a range of neural insults, but their application in Alzheimer's disease (AD) is still limited and the mechanisms underlying the cognitive benefits of stem cells remain to be elucidated. Here, the effects of clinical‐grade human umbilical cord‐derived mesenchymal stem cells (hUC‐MSCs) on the recovery of cognitive ability in SAMP8 mice, a senescence‐accelerated mouse model of AD is explored. A functional assay identifies that the core functional factor hepatocyte growth factor (HGF) secreted from hUC‐MSCs plays critical roles in hUC‐MSC‐modulated recovery of damaged neural cells by down‐regulating hyperphosphorylated tau, reversing spine loss, and promoting synaptic plasticity in an AD cell model. Mechanistically, structural and functional recovery, as well as cognitive enhancements elicited by exposure to hUC‐MSCs, are at least partially mediated by HGF in the AD hippocampus through the activation of the cMet‐AKT‐GSK3 β signaling pathway. Taken together, these data strongly implicate HGF in mediating hUC‐MSC‐induced improvements in functional recovery in AD models. Abstract : This study explores the effects of clinical‐grade hUC‐MSCs on the recovery of cognitive ability of Alzheimer's disease (AD). All results uncover that HGF secreted from hUC‐MSCs, mediates the beneficial effects of hUC‐MSCs on functional recovery of damaged neural cells by downregulating hyperphosphorylated tau, improving neurofibrillary tangles, reversing spine loss, and promoting synaptic plasticity in AD hippocampus through the cMet‐AKT‐GSK3 β signaling pathway.